1981
DOI: 10.1111/j.2044-8295.1981.tb02160.x
|View full text |Cite
|
Sign up to set email alerts
|

Visual‐motor localizations in normal and subnormal development

Abstract: Subnormal and normal children, of like mental age, were compared on a visual target localization task. Severely subnormal children were found to be less accurate than normal children, in conditions where they visually directed or visually guided their hand to the target and received visual knowledge of results. On visually directed localizations without knowledge of results or with proprioceptive knowledge of results (same hand) no significant difference was found between normal and severely subnormal children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
5

Year Published

1981
1981
1992
1992

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 1 publication
1
2
0
5
Order By: Relevance
“…The present experiments show that whereas visual and motor movements can share a common representation, nevertheless the efficiency of storage of information from these two sensory modalities is differential and to some extent sensory specific. agreement with results obtained from target pointing experiments (Anwar, 1981~). In these experiments on visual-motor localization, visual knowledge of results could not be effectively used by severely subnormal children.…”
Section: Perceptual Integrationsupporting
confidence: 78%
See 1 more Smart Citation
“…The present experiments show that whereas visual and motor movements can share a common representation, nevertheless the efficiency of storage of information from these two sensory modalities is differential and to some extent sensory specific. agreement with results obtained from target pointing experiments (Anwar, 1981~). In these experiments on visual-motor localization, visual knowledge of results could not be effectively used by severely subnormal children.…”
Section: Perceptual Integrationsupporting
confidence: 78%
“…However, we have some evidence to suggest that a motor deficit alone cannot be regarded as the crucial factor responsible for poor performance on perceptual-motor tasks (Anwar & Hermelin, 1979;Anwar, 1981u, b). For example, in three-dimensional space, Down's syndrome and non-Down's syndrome adolescents were able to improve their visual-motor target localizations when they could manually feel the extent of their error (Anwar, 1981~). Such visual-target localizations did not improve when the error information was only visually available to the child.…”
mentioning
confidence: 95%
“…In recent experiments on visual-motor target localisations (Anwar, 1979a) evidence was obtained which tended to support a hypothesis of proprioceptive over visual dominance in Down's syndrome subjects. It was found that under conditions of visual direction (where a target can be seen but the pointing hand cannot) Down's syndrome children were able to improve accuracy significantly when given proprioceptive feedback but not when given visual error information.…”
Section: Introductionmentioning
confidence: 93%
“…Σύµφωνα µε την Anwar (1981), τα παιδιά µε σοβαρή καθυστέρηση γενικά έχουν φτωχές οπτικο-κινητικές ικανότητες. Μια υποθετική εξήγηση, η οποία δόθηκε απ' τον Abercrombie (1970), είναι ότι ίσως τα σοβαρά νοητικά καθυστερηµένα παιδιά δίνουν αντικρουόµενη προσοχή σε οπτικές και ιδιοδεκτικές εισόδους.…”
Section: λεπτές αντιληπτικο-κινητικές δεξιότητες των νοητικά καθυστερηµένωνunclassified
“…Στη µελέτη της Anwar (1981) συγκρίθηκαν µέτρια και σοβαρά νοητικά καθυστερηµένα παιδιά µε τυπικώς αναπτυσσόµενα παιδιά ίδιας νοητικής ηλικίας σ' ένα βασικό οπτικο-κινητικό έργο εντοπισµού του οπτικού στόχου. Τα αποτελέσµατα των πειραµάτων της δείχνουν ότι τα παιδιά µε σοβαρή νοητική καθυστέρηση ήταν λιγότερο ακριβή απ' τα τυπικώς αναπτυσσόµενα παιδιά, σε συνθήκες όπου καθοδηγούσαν οπτικά το χέρι τους στο στόχο και λάµβαναν οπτική γνώση των αποτελεσµάτων.…”
Section: επιδόσεις σε έργα ακρίβειας-στόχευσηςunclassified